Morphological characterization and phylogeny of pythium and related genera in rayong province, thailand - Saelee, Rattasit; Busarakam, Kanungnid; Koohakan, Prommart (My University, 2021)
Most well-known microorganisms in the class Oomycetes (notably genera Phytophthora and Pythium) are pathogenic to both animals and plants due to their diverse lifestyle patterns. This study was designed to recover Pythium from composite soils (cultivated and forest soils) and water sources (fresh and brackish water) from Rayong Province. Twenty isolates of hyaline and non-septate fungal-like organisms were isolated from those sources. The primer pair ITS4 and ITS6 were used to amplify approximately 900 bp products from Internal transcribed spacer (ITS) region and morphological characteristics including sporangium, oogonium, antheridium and oospore, were noted. Morphological characteristics data of recovered Pythium strain can be classified into 12 source groups. ITS sequencing results revealed that eight closely related species had been recovered: Globisporangium splendens, Pythium cucurbitacearum, Pythium acanthichum, Pythium deliense, Pythium diclinum, Pythium torulosum, Phytopythium vexans and Phytopythium helicoides, which had similarities in the range 94.67-100% values at between 656 and 922 locations. Most of these species were reported as plant pathogens. Therefore, this report can be used as a guide for disease control planning.
Keywords: Identification; Oomycetes; Phylogeny; Pythium; Rayong Province